Immune Dysregulation in Patients With Chromosome 18q Deletions—Searching for Putative Loci for Autoimmunity and Immunodeficiency - Hogendorf, Anna; Zieliński, Maciej; Constantinou, Maria; Śmigiel, Robert; Wierzba, Jolanta; Wyka, Krystyna; Wędrychowicz, Anna; Jakubiuk-Tomaszuk, Anna; Budzynska, Edyta; Piotrowicz, Malgorzata; Lipska-Ziętkiewicz, Beata S.; Kaczorowska, Ewa; et al. (Frontiers in Immunology, 2021)
Introduction: Autoimmune disorders, IgA deficiency and allergies seem to be common among individuals with 18 q deletion syndrome [OMIM 601808]. We aimed to determine the prevalence, mechanism and genetic background of autoimmunity, immune deficiency and allergy in a cohort of patients with 18q deletions. Material and methods: Medical registries and social media were used to recruit the patients. Microarray oligonucleotide comparative genomic hybridization (aCGH) (Agilent, USA) was performed in all patients to identify size and location of chromosome 18 deletion. Clinical evaluation and medical records collection were performed in each of the study participants. The history of autoimmune disorders, severe and/or recurrent infections and symptoms of allergy was noted. Total immunoglobulin IgG, IgA, IgM, IgE and IgG1-4 serum levels were measured by nephelometry and ELISA methods. Lymphocyte subsets phenotyping was performed in 24 subjects from 18q del cohort. To predict the most promising candidate genes we used the ENDEAVOUR - a free web resource for gene prioritization. Results: 18q deletion was confirmed by array CGH analysis in 27 individuals, 15(55.6%) females and 12 males, referred to the project by specialists in medical genetics, diabetology or pediatric endocrinology between May 2015-December 2019. The mean age at examination was 11.8 (min-max:4.0-33.5) years. Autoimmune disorders were present in 14/27 (51.8%) of the cohort. In 8 of patients symptoms of immune deficiency coexisted with autoimmunity. Allergy was reported in 9/27 (33.4%) patients. Over 89% of patients presented with at list one type of immunoglobulin (IgA, M, G, E and IgG1-4 ) deficiency and 8/25 (32%) had abnormalities in at least two major immunoglobulin (IgG, IgA, IgM) measurements (CVID-like phenotype). Patients with 18q del exhibited significantly decreased CD4, Treg FOXP3+, TregFOXP3+Helios+, TemCD4 cell numbers in comparison to control groups of 24 T1DM patients and 28 healthy controls. Conclusions: Patients with 18q deletions frequently suffer from autoimmune disorders, recurrent infections and allergy due to immune dysregulation presenting with variable antibody deficiencies and T regulatory cells deficiency (CD4+CD25+CD127lowFOXP3+). The spectrum of speculations regarding which gene might be responsible for such phenotype range from single gene haploinsufficiency to deletion of a cluster of immunogenes located distally to 18q21.